Psychotherapy for mental health symptoms and disorders in elite athletes: a narrative review. Issue 12 (3rd June 2019) - Stillman, Mark A; Glick, Ira D; McDuff, David; Reardon, Claudia L; Hitchcock, Mary E; Fitch, Vincent M; Hainline, Brian
Abstract : Background: Athletes, like non-athletes, suffer from mental health symptoms and disorders that affect their lives and their performance. Psychotherapy, either as the sole treatment or combined with other non-pharmacological and pharmacological strategies, is a pivotal component of management of mental health symptoms and disorders in elite athletes. Psychotherapy takes the form of individual, couples/family or group therapy and should address athlete-specific issues while being embraced as normative by athletes and their core stakeholders. Main findings: This narrative review summarises controlled and non-controlled research on psychotherapy for elite athletes with mental health symptoms and disorders. In summary, treatment is similar to that of non-athletes—although with attention to issues that are athlete-specific. Challenges associated with psychotherapy with elite athletes are discussed, including diagnostic issues, deterrents to help-seeking and expectations about services. We describe certain personality characteristics sometimes associated with elite athletes, including narcissism and aggression, which could make psychotherapy with this population more challenging. The literature regarding psychotherapeutic interventions in elite athletes is sparse and largely anecdotal.